Characteristics of the Occlusal Plane Associated with Unilateral and Bilateral Articular Eminence Inclination: A Cross-Sectional CBCT Study - Fátima Erandi Camacho-Álvarez; Silvia Paulina Martínez-Contreras; Jacqueline A. Rodríguez-Chávez; Gerardo Martínez-Suárez; Álvaro Edgar González-Aragón Pineda; Ronald Roossevelt Ramos-Montiel; Carla Monserrat Ramírez-Martínez; Sergio Sánchez-García; Luis Pablo Cruz-Hervert; María Eugenia Jiménez-Corona (Dentistry Journal)
The characteristics of the temporomandibular joint (TMJ) are essential in orthodontic and prosthetic treatments. Previous studies have suggested an association between articular eminence inclinations (AEI) and occlusal plane characteristics using radiographs, but no bilateral analysis has been conducted using cone beam computed tomography (CBCT). Objective: This study aimed to investigate the specific characteristics of the occlusal plane inclinations associated with unilateral and bilateral AEI using CBCT. Methods: We conducted a cross-sectional study to evaluate 200 temporomandibular joints (TMJs) from 100 records obtained at the orthodontic department. We evaluated the association between the AEI, and occlusal plane characteristics like the cant of the occlusal angle, occlusal plane angles, inclination of the upper incisor to the Frankfort plane and palatal plane using both bivariate and multivariate analyses both unilaterally and bilaterally. Results: Our findings suggested statistically significant associations (p < 0.050) between AEI (bilateral) and occlusal inclination parameters, including the cant of the occlusal plane (Coef. −0.38; 95%CI −0.70:−0.06; p = 0.017), occlusal plane angle (Coef. −0.39; 95%CI −0.740:−0.05; p = 0.024), and position of the upper incisor relative to the palatal plane (Coef. −0.34; 95%CI −0.63:−0.06; p = 0.016). Conclusion: This study suggests an association between dental inclinations and AEI, which reflects the anatomical characteristics of TMJ and its related dental structures.